A method of applying compressive pre‐stress to AlGaN barrier in AlGaN/GaN heterostructures by depositing an additional thermally mismatched dielectric. Issue 9 (28th April 2016) - Liu, Yanli; Chen, Dunjun; Yang, Lianhong; Lu, Hai; Zhang, Rong; Zheng, Youdou
Abstract : To mitigate strain relaxation of AlGaN barrier in AlGaN/GaN heterostructures, a new method is proposed by inducing an additional biaxial compressive pre‐stress. Here, MgO dielectric with a twice larger thermal‐expansion coefficient than AlGaN was deposited on the surface of Si3 N4 ‐passivated AlGaN/GaN heterostructures at high temperature to demonstrate this idea. The ultraviolet Raman results verify that MgO dielectric introduced a temperature‐dependent biaxial compressive stress to the AlGaN barrier. The calculated variations of two‐dimensional‐electron‐gas concentration before and after depositing the MgO dielectric according to piezoelectric polarization theory are in good agreement with those from Hall effect measurements in the temperature range of 80–600 K, which further confirms the presence of the additional compressive pre‐stress to AlGaN.